2013
DOI: 10.1016/j.peptides.2013.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Oral Angiotensin-(1–7) prevented obesity and hepatic inflammation by inhibition of resistin/TLR4/MAPK/NF-κB in rats fed with high-fat diet

Abstract: Obesity is characterized by a pro-inflammatory state commonly associated with type 2 diabetes and fat-liver disease. In the last few years, different studies pointed out the role of Angiotensin (Ang)-(1-7) in the metabolic regulation. The aim of the present study was to evaluate the effect of oral-administration of Ang-(1-7) in metabolism and inflammatory state of high-fat feed rats. Twenty-four male Sprague Dawley rats were randomized into three groups: High Fat Diet (HFD); Standard Diet (ST); High Fat Diet+A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(75 citation statements)
references
References 30 publications
3
65
1
2
Order By: Relevance
“…This alludes to an adaptation, which is lost upon repeated and/or sustained exposure to hepatotoxic stimuli leading to NAFLD and steatohepatitis. Furthermore, the constitutive activation of NF-κB has been associated with severe hepatic and moderate peripheral insulin resistance (53). The present data suggest that a single PO challenge promotes pathways of LPSand TLR4-mediated inflammation and cytotoxicity, which are buffered by the activation of NF-κB, which in turn contributes to insulin resistance.…”
Section: Figure 2 Time Courses Of Circulating Metabolites and Hormonmentioning
confidence: 54%
“…This alludes to an adaptation, which is lost upon repeated and/or sustained exposure to hepatotoxic stimuli leading to NAFLD and steatohepatitis. Furthermore, the constitutive activation of NF-κB has been associated with severe hepatic and moderate peripheral insulin resistance (53). The present data suggest that a single PO challenge promotes pathways of LPSand TLR4-mediated inflammation and cytotoxicity, which are buffered by the activation of NF-κB, which in turn contributes to insulin resistance.…”
Section: Figure 2 Time Courses Of Circulating Metabolites and Hormonmentioning
confidence: 54%
“…Like ACE inhibitors or AT 1 receptor blockers, ANG-(1-7) attenuates the characteristics of metabolic syndrome (49). Oral formulation of ANG-(1-7) improves metabolism, and decreases the proinflammatory profile and fat deposition in HFD-fed mice as well as hypertensive rats (50,51). Prolonged ANG-(1-7) treatment has also been shown to improve endothelial dysfunction and oxidative stress in a mouse model of obesity (52).…”
Section: Discussionmentioning
confidence: 99%
“…Diverging from many reports describing Mas-mediated anti-inflammatory effects in different tissues (Al-Maghrebi et al, 2009;da Silveira et al, 2010;El-Hashim et al, 2012;Giani et al, 2012;Jiang et al, 2012;Santos et al, 2012;Souza and Costa-Neto, 2012;Sukumaran et al, 2012;Chen et al, 2013;Feltenberger et al, 2013;Moore et al, 2013;Regenhardt et al, 2013;Wagenaar et al, 2013;Wang et al, 2013c;Acuna et al, 2014;Meng et al, 2014), in the kidney, a proinflammatory role for Ang-(1-7) and Mas was reported by using a model of unilateral ureteral obstruction in mice (Esteban et al, 2009). In contrast, anti-inflammatory and beneficial effects of Ang-(1-7) were observed in other models of kidney injury (Singh et al, 2010b;Moon et al, 2011;Bernardi et al, 2012;Giani et al, 2012;Harris, 2012;Chou et al, 2013;Santos et al, 2013b;Zhang et al, 2014). Interestingly, the outcome of adriamycin-induced nephropathy was similar in Mas-KO and wild-type mice.…”
Section: Mas-related G Protein-coupled Receptors and Mas In Cardiomentioning
confidence: 96%